Knowledge of english language as a predictor of students cognitive achievement in senior secondary school mathematics (2011)
In this paper, the authors, using ex-post-facto procedure, attempted to show the effect of knowledge of English language on students' cognitive achievement in senior secondary school mathematics. In all 504 SS II students, comprising 252 males and 252 females were sampled, using cluster sampling technique. Using simple regression analysis, the findings showed that knowledge of English language appears to be a predictor of students cognitive achievement in mathematics even irrespective of gender. The implications of the study as well as suggestions for improving the teaching and learning of mathematics at the senior secondary school level were highlighted.